2020
DOI: 10.1097/pra.0000000000000439
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Dialectical Behavior Therapy for Treating Problematic Interactive Media Use

Abstract: Over the past decade, clinicians have observed an increase in adolescents overusing interactive media, resulting in detrimental consequences such as disrupted sleep, inattention to academic tasks, and deterioration of social relationships. The recognition of problematic interactive media use (PIMU), the excessive and dysregulated use of interactive electronic media that affects mental and physical health, resulting in difficulty meeting developmentally appropriate functional capacity, has led to a call for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…DBT has been demonstrated to improve outcomes in patients with substance use disorders. 18,20,21 The main results of this study are as follows: the study group, who received distress tolerance skills training, demonstrated an increase in their tolerance toward distress levels at post-treatment and at the 3-month follow-up. The study group exhibited a significant decrease in problematic internet use scores across all subscales (obsession, neglect, control disorders) post-treatment, and this reduction was sustained for three months.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…DBT has been demonstrated to improve outcomes in patients with substance use disorders. 18,20,21 The main results of this study are as follows: the study group, who received distress tolerance skills training, demonstrated an increase in their tolerance toward distress levels at post-treatment and at the 3-month follow-up. The study group exhibited a significant decrease in problematic internet use scores across all subscales (obsession, neglect, control disorders) post-treatment, and this reduction was sustained for three months.…”
Section: Discussionmentioning
confidence: 88%
“…DBT has been demonstrated to improve outcomes in patients with substance use disorders. 18 , 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are reasons to hypothesize a contributory link between certain types of SMU and declining mental health (eg, SMU that displaces face-to-face social interactions and leads to increased social isolation and loneliness), underlying mental or behavioral health issues may actually drive high-frequency SMU. In fact, young people with certain behavioral health conditions-especially attention-deficit/hyperactivity disorder, social anxiety disorder, autism spectrum disorder, and depression-use screen media more and are predisposed to problematic interactive media use, characterized by a clinically relevant decline in one's functional status [34][35][36][37][38][39][40][41][42]. Underlying mental health conditions may also amplify or otherwise alter the effects of SMU.…”
Section: Overviewmentioning
confidence: 99%